2003
DOI: 10.1172/jci200319246
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is associated with macrophage accumulation in adipose tissue

Abstract: Obesity alters adipose tissue metabolic and endocrine function and leads to an increased release of fatty acids, hormones, and proinflammatory molecules that contribute to obesity associated complications. To further characterize the changes that occur in adipose tissue with increasing adiposity, we profiled transcript expression in perigonadal adipose tissue from groups of mice in which adiposity varied due to sex, diet, and the obesity-related mutations agouti (Ay) and obese (Lepob). We found that the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

145
2,775
9
80

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 7,518 publications
(3,009 citation statements)
references
References 92 publications
145
2,775
9
80
Order By: Relevance
“…This study revealed that the human ATM is characterized by high expression of MR, CD163 and integrin avb5. Moreover, the data support the model of obesity-associated macrophage infiltration of the AT 2,3,[26][27][28] by showing that the abundance of CD14 pos MR pos ATMs correlates with the BMI. As a secondary outcome of this study, human M2 macrophages were for the first time thoroughly analyzed regarding surface protein expression thus corroborating other studies mainly investigating gene expression and/or murine cells.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This study revealed that the human ATM is characterized by high expression of MR, CD163 and integrin avb5. Moreover, the data support the model of obesity-associated macrophage infiltration of the AT 2,3,[26][27][28] by showing that the abundance of CD14 pos MR pos ATMs correlates with the BMI. As a secondary outcome of this study, human M2 macrophages were for the first time thoroughly analyzed regarding surface protein expression thus corroborating other studies mainly investigating gene expression and/or murine cells.…”
Section: Discussionsupporting
confidence: 77%
“…1 These chronic inflammatory alterations are associated with increased abundance of macrophages in adipose tissue (AT). [2][3][4] Adipose tissue macrophages (ATMs)…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, two separate reports have shown that adipose tissue is characterised by macrophage infiltration, which could affect its normal function and inflammatory properties [33,34]. In this regard, we show that although adiposity is increased in Alox5 −/− mice from as early as 12 weeks of age, the expression of inflammatory genes in adipose tissue is lower.…”
Section: Discussionsupporting
confidence: 51%
“…Obesity is recognized as a chronic, systemic proinflammatory state involving the same cytokines that have been implicated in OA 36. Adipose tissue in obese individuals and in animal models contains increased numbers of activated macrophages that release proinflammatory cytokines such as IL‐1β, TNF, and IL‐6 37. These elevated cytokine levels promote proinflammatory changes in adipocytes that, in turn, release additional proinflammatory mediators and adipokines to amplify the inflammatory response and act both locally on adipocytes and systemically to impair insulin action in insulin target tissues 23, 24.…”
Section: Discussionmentioning
confidence: 99%